Directions for Improving the Food Market in the Fergana Region - Sotvoldiev Nodirbek Jurabaevich (Research Parks Publishers, 2021)
The article reveals the domestic potential of food production in the Fergana region. A set of measures to be implemented in the Fergana region to achieve the strategic indicators of agricultural development of the Republic of Uzbekistan for 2020-2030 has been developed. Scientific proposals and practical recommendations aimed at improving the regional food market are given.